Analysis of MicroRNAs Associated With Carotid Atherosclerotic Plaque Rupture With Thrombosis - Nie, Peng; Yang, Fan; Wan, Fang; Jin, Shuxuan; Pu, Jun (Frontiers in Genetics, 2021)
Atherosclerosis is a progressive vascular wall inflammatory disease, and the rupture of atherosclerotic vulnerable plaques are the leading cause of morbidity and mortality worldwide. This study intended to explore the potential mechanisms behind plaque rupture and thrombosis in ApoE knockout mice. The spontaneous plaque rupture models were established, and left carotid artery tissues at different time points (1-, 2-, 4-, 6-, 8-, 12- and 16-week post-surgery) were collected. By the extent of plaque rupture, plaque was defined as 1) control groups, 2) atherosclerotic plaque group, and 3) plaque rupture group. Macrophage (CD68), MMP-8, and MMP-13 activities were measured by immunofluorescence. Cytokines and inflammatory markers were measured by ELISA. The left carotid artery samples tissue was collected to evaluate the miRNAs expression level by miRNA-microarray. Bioinformatic analyses was conducted at three levels: 2) vs. 1), 3) vs. 2), and again in 7 time series analysis. The plaque rupture with thrombus and intraplaque hemorrhage results peaked at 8 weeks, and decreased thereafter. Similar trends were seen in the number of plaque macrophages and lipids, the expression of matrix metalloproteinase, and the atherosclerotic and plasma cytokine levels. MiRNA-microarray showed that miR-322-5p and miR-206-3p was specifically up-regulated in atherosclerotic plaque group compared with control group. Meanwhile, miR-466h-5p was specifically up-regulated in plaque rupture group compared with atherosclerotic plaque group. The highest incidence of plaque rupture and thrombosis occurred at 8 weeks post-surgery. miR-322-5p and miR-206-3p may be associated with the formation of atherosclerotic plaques. miR-466h-5p may promote atherosclerotic plaque rupture via apoptosis-related pathways.